PO.5.113 C3 and C1Q deposition in different kidney compartments is not associated with serious infections in lupus nephritis. (27th September 2022) - Knezevic, T; Padjen, I; Ivkovic, V; Laganovic, M; Jezic, I; Biloglav, Z; Bulimbasic, S; Coric, M; Mayer, M; Anic, B
Abstract : Purpose: Complement activation is an important step in the mechanism of tissue damage in lupus nephritis (LN). Complement deposition in kidney tissue might reflect different immunologic processes and higher disease severity and result in adverse outcomes, but very few studies explored these potentially important associations. Given these immunologic consequences, we have postulated that complement deposition in the kidney might be associated with higher risk for serious infections in LN. Methods: We have conducted a retrospective cohort study to evaluate the prognostic significance of C1q and C3 complement factors in renal tissue compartments for the occurrence of serious infections. We have collected data on demographics, clinical and laboratory parameters and histopathology (light, immunofluorescent and electron microscopy) at the time of biopsy and after long-term follow-up. Serious infections were defined as those that: 1. require intravenous therapy OR 2. lead to hospitalization OR 3. have resulted in death in 30 days from diagnosis. C1q and C3 expression graded in different kidney compartments (mesangium, glomerular basement membrane (GBM), tubular basement membrane (TBM) and peripheral capillary wall) as 0 to 3+ and another analysis was performed with dichotomized grading as 0 (absent) and 1+ to 3+ (present). SLE was diagnosed using the American College of Rheumatology criteria. Results: A total of 51 patients with biopsy-proven LN were followed up for 4.5±2.9 years (80% women, mean age at biopsy 38±14). Of these, 22 (43%) had at least one episode of serious infection with 4 patients having 2 episodes. Complement expression in different kidney compartments was as follows: mesangium (C1q 54%, C3 59%), GBM (C1q 34%, C3 41%), TBM (C1q 5%, C3 5%) and blood vessel wall (C1q 0%, C3 5%). There was no difference in the distributions of mesangial (present vs. absent, 80% vs. 78%, p>0.99), GBM (53% vs. 38%, p=0.53), TBM (20% vs. 5%, p=0.17) and peripheral capillary wall C3 deposition (25% vs. 35%, p=0.53) or mesangial (75% vs. 65%, p=0.53), GBM (47% vs. 33%, p=0.52), TBM (5% vs. 5%, p>0.99) and peripheral capillary wall C1q deposition (25% vs. 30%, p=0.75). Conclusions: Complement deposition in kidney tissue, while an underexplored and potentially important process, was not associated with serious infections in LN.